Differential Prediction in the Use of the SAT and High School Grades in Predicting College Performance: Joint Effects of Race and Language. Issue 3 (18th May 2017) - Shewach, Oren R.; Shen, Winny; Sackett, Paul R.; Kuncel, Nathan R.
Abstract : The literature on differential prediction of college performance of racial/ethnic minority students for standardized tests and high school grades indicates the use of these predictors often results in overprediction of minority student performance. However, these studies typically involve native English‐speaking students. In contrast, a smaller literature on language proficiency suggests academic performance of those with more limited English language proficiency may be underpredicted by standardized tests. These two literatures have not been well integrated, despite the fact that a number of racial/ethnic minority groups within the United States contain recent immigrant populations or heritage language speakers. This study investigates the joint role of race/ethnicity and language proficiency in Hispanic, Asian, and White ethnic groups across three educational admissions systems (SAT, HSGPA, and their composite) in predicting freshman grades. Our results indicate that language may differentially affect academic outcomes for different racial/ethnic subgroups. The SAT loses predictive power for Asian and White students who speak another best language, whereas it does not for Hispanic students who speak another best language. The differential prediction of college grades of linguistic minorities within racial/ethnic minority subgroups appears to be driven by the verbally loaded subtests of standardized tests but is largely unrelated to quantitative tests.